A Qualitative Evaluation of Smoke-Free Policy Implementation among the Hospitality Industry in Yogyakarta, Indonesia - Sutantri; Sugiyo, Dianita; Sutrisno, Resti Yulianti; Aditjondro, Enrico; Wulandari, Bertha Tesma; Wandasari, Noven Tri; Rachmawati, Riska Putri; Wandasari, Arumi (Public Health of Indonesia, 2024)
Background: The Indonesian government has implemented various regulations, including smoke-free policies (SFPs) aimed at reducing exposure to second-hand smoke and improving public health. However, the implementation of these policies has encountered challenges. Objective: This study aimed to investigate the implementation of SFP in the hospitality industry in Yogyakarta, Indonesia. Methods: Three focus group discussions with the managers of hotels, restaurants, and coffee shops (n=19) were conducted in November 2021. Thematic analysis was used to analyse the data. Results: Three themes were identified: 1) Efforts to implement SFPs at hospitality premises; 2) Reasons for adopting SFPs; and 3) Challenges for policy implementation. Many hospitalities industry have undertaken efforts to implement SFPs, though they are not comprehensive. The reasons for implementing SFPs include protecting second-hand smokers, meeting guest preferences, and creating a fresher environment. Resistance from customers has become a significant challenge, as some view SFPs as an infringement on personal freedom. Furthermore, unclear sanctions and enforcement from the government also highlighted by participant as the main barriers of SFPs implementation. Conclusion: Overall, while there is significant effort to implement SFPs in hospitality venues, challenges such as customer resistance and unclear government guidance persist. This condition underscores the need for clearer policies and support mechanisms for successful implementation.